Anterior cruciate ligament reconstruction simultaneously with trans-tibial pull-out fixation of avulsion fracture of medial and lateral meniscus posterior roots: a case report and eight-year follow-up - Yingchang Pang; Sibo Xu; Gengxian Xiang; Kaiqi Zhang; Tiezheng Sun (BMC Musculoskeletal Disorders)
Abstract We report a rare case of anterior cruciate ligament (ACL) tear combined with acute avulsion fracture of the medial and lateral meniscal posterior roots in a 23-year-old male patient. The management strategy was focused on how to do arthroscopic trans-tibial pull-out fixation of the avulsed fracture fragment and ACL reconstruction simultaneously, avoiding the possibility of the tibia tunnel interference during drilling. At the 8-year postoperative follow-up, the patient demonstrated excellent knee function and returned to non-competitive football activities, and manual knee laxity tests were negative. Plain radiographs of the knee showed complete bone healing of the avulsed fracture fragment without osteophyte formation and joint space narrowing. Magnetic resonance imaging showed good ACL graft integrity, and the tibial fragment was connected with the native insertion site.